Ulva prolifera Extract Alleviates Intestinal Oxidative Stress via Nrf2 Signaling in Weaned Piglets Challenged With Hydrogen Peroxide - Feng, Yanzhong; An, Zhimin; Chen, Heshu; He, Xinmiao; Wang, Wentao; Li, Xiang; Zhang, Haifeng; Li, Fenglan; Liu, Di (Frontiers in Immunology, 2020)
Background Ulva prolifera extract contains a variety of functional active substances. Whether these substances had any beneficial effects on the small intestine of weaned piglets under oxidative stress remained unknown. Method We explored the effects of U. prolifera extract on oxidative stress and related mechanisms in weaned piglets and intestinal porcine epithelial cells (IPEC-J2) challenged with hydrogen peroxide. Results U. prolifera extract was found to mainly consist of polyphenols and unsaturated fatty acids. U. prolifera extract increased total antioxidant capacity and superoxide dismutase (SOD) activity, while it decreased malondialdehyde content, in the serum of weaned piglets challenged with hydrogen peroxide. Moreover, U. prolifera extract increased mRNA expression of SOD and catalase, as well as the intestinal expression of nuclear NF-E2-related factor 2 (Nrf2), both in vitro and in vivo. Furthermore, U. prolifera extract decreased reactive oxygen species and improved mitochondrial respiration in IPEC-J2 cells treated with hydrogen peroxide. However, AMPK inhibition did not affect nuclear Nrf2 expression and only partially affected the effects of U. prolifera extract on oxidative stress. Conclusion We suggest that U. prolifera extract alleviates oxidative stress via Nrf2 signaling, but independent of AMPK pathway in weaned piglets challenged with hydrogen peroxide. These results shed new insight into the potential applications of U. prolifera extract as a therapeutic agent for the prevention and treatment of oxidative stress-induced intestinal diseases.